Transthoracic echocardiographic mensuration of two-dimensional left atrial to aorta ratios and left ventricular M-mode parameters in clinically normal adult Dachshunds - Kirberger, Robert M. (University of Pretoria, 2015)
Dissertation (MMedVet)--University of Pretoria, 2014.